2003
DOI: 10.3748/wjg.v9.i2.219
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative TN staging of esophageal cancer: Comparison of miniprobe ultrasonography, spiral CT and MRI

Abstract: MPS is superior to spiral CT or MRI for T staging, especially in early esophageal cancer. However, the three modalities have the similar accuracy in N staging. Spiral CT or MRI is helpful for the detection of far-distance metastasis in esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 63 publications
0
47
1
5
Order By: Relevance
“…For T staging, there were 43 studies [10,18,[20][21][22][23][24] . There were 44 studies for nodal staging [10,18,[20][21][22][23][24][38][39][40][41][42][43][44][45][46][48][49][50]53,54,[56][57][58][59][60][61][62][63][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] , and of these, 4 used FNA for nodal staging [23,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For T staging, there were 43 studies [10,18,[20][21][22][23][24] . There were 44 studies for nodal staging [10,18,[20][21][22][23][24][38][39][40][41][42][43][44][45][46][48][49][50]53,54,[56][57][58][59][60][61][62][63][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] , and of these, 4 used FNA for nodal staging [23,…”
Section: Resultsmentioning
confidence: 99%
“…With EUS emerging as a very useful staging tool, its role in staging esophageal cancer continues to be addressed. Several studies have identified the potential benefits of EUS with esophageal cancer staging; however, results regarding the extent of its benefits have been inconsistent [52,72,82] . We conducted a meta-analysis to examine the role of EUS in the staging of esophageal cancer for loco-regional spread.…”
Section: Introductionmentioning
confidence: 99%
“…For CT, the literature search gave 1091 hits. Seventeen articles on CT for regional lymph node metastases met the inclusion criteria (Quint et al, 1985;Botet et al, 1991;Ziegler et al, 1991;Sondenaa et al, 1992;Greenberg et al, 1994;Yoshikane et al, 1994;Flanagan et al, 1997;Nishimaki et al, 1999;Choi et al, 2000;Wren et al, 2002;Rasanen et al, 2003;Vazquez-Sequeiros et al, 2003;Wu et al, 2003;Yoon et al, 2003;Heeren et al, 2004;Sihvo et al, 2004;Lowe et al, 2005). As some articles containing the results of CT not only reported on celiac lymph node metastases, but also on other abdominal lymph node metastases, we decided to include all articles (five in total) with these results (Quint et al, 1985;Becker et al, 1986;Watt et al, 1989;Van Overhagen et al, 1993;Parmar et al, 2002).…”
Section: Literature Search and Data Extractionmentioning
confidence: 99%
“…In total, 31 articles on EUS for regional lymph node metastases (Tio et al, 1990;Botet et al, 1991;Rice et al, 1991;Ziegler et al, 1991;Dittler and Siewert, 1993;Grimm et al, 1993;Greenberg et al, 1994;Yoshikane et al, 1994;Binmoeller et al, 1995;Hasegawa et al, 1996;Hunerbein et al, 1996;Natsugoe et al, 1996;Pham et al, 1998;Vickers, 1998;Bowrey et al, 1999;Catalano et al, 1999;Nishimaki et al, 1999;Salminen et al, 1999;Choi et al, 2000;Nesje et al, 2000;Richards et al, 2000;Shinkai et al, 2000;Vazquez-Sequeiros et al, 2001Rasanen et al, 2003;Wu et al, 2003;Heeren et al, 2004;Sihvo et al, 2004;DeWitt et al, 2005;Lowe et al, 2005;Pedrazzani et al, 2005) and five articles on EUS for celiac lymph node metastases were included (Binmoeller et al, 1995;Catalano et al, 1999;Eloubeidi et al, 2001;Vazquez-Sequeiros et al, 2001;Parmar et al, 2002) (Table 1). For CT, the literature search gave 1091 hits.…”
Section: Literature Search and Data Extractionmentioning
confidence: 99%
“…In the literature, CT and MRI both show low accuracy compared to EUS to determine T stage (45% and 60%, respectively). 10,11 Therefore, it was investigated in the present study whether performing bronchoscopy after EUS has any additional value. In this study, bronchoscopy did not detect any patients with airway invasion that was not already detected by EUS.…”
Section: Discussionmentioning
confidence: 99%